Puppetry As A Platform For Body Safety Awareness Campaign - Md. Khir , Roselina Johari; Pawanteh , Murina; Stephens , John; Alhabshi SM, Sharifah Fatmah (Advances in Social Sciences Research Journal, 2019)
This study focused on how puppetry is used as a communication platform to send out key messages to primary school children from the age of 7 to 12 years old on body safety awareness. This Action Research was done through a Communication Media Studies Course in the School of Communication and Creative Arts, KDU UC to investigate how the use of puppetry is able to create awareness in body safety among primary school students. Communicating about body safety towards children has always been an issue due to the topic that is related to their private parts. This topic has been recognised as taboo for both parents and teachers in Malaysia although the issue of perpetrators on sexual grooming or child grooming has been rising in the country. Ten students from each session were selected by the teachers and consented by the parents for a face to face interview to get their impression on the puppet shows and whether they had understood the message sent out by the puppet theatre performance. The sessions were recorded through a voice recorder. We found that the students were positively and emphatically inclined towards the stories written by us about what constitutes sexual inappropriateness and highly understood the specific strategies to help them avoid or cope with bad situations